PENGARUH PERBANDINGAN ANTARA MODEL PEMBELAJARAN DIRECT INSTRUCTION DENGAN MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR BACKHAND PADA SISWA KELAS IV SD NEGERI CIPAKU KECAMATAN SUKARAJA - Elan Suherlan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Teaching and learning process is a very complex process. In order for the learning process to achieve results that are in accordance with the objectives, teachers need to consider and choose effective teaching strategies. There are still many Physical Education teachers who have not used the Direct Instruction and Project Based Learning models in Physical Education subjects because they do not understand, are lazy, and do not want to try, are busy, low learning outcomes do not reach the Minimum completeness Criteria and the teacher does not like this teaching style. This study aims to determine the difference in influence between the direct instruction model and the project based learning model on the improvement of backhand learning outcomes for fourth grade students at Cipaku Elementary School The method that will be used by the writer is an experimental method. Then the design used in this study is the Randomize Pretest-Posttest Control Goup Design. The population of this research is all fourth grade students of Cipaku Public Elementary School. The results obtained in accordance with the hypothesis that the authors propose obtained an answer that there are differences in the effect between the direct instruction model and the project based learning model on the improvement of backhand learning outcomes in fourth grade students at Cipaku Elementary School